Knowledge and attitude of parents with regard to avulsed permanent tooth of their children and their emergency management-Chennai - Tee Jing Loo; Deepa Gurunathan; Sujatha Somasundaram (Wolters Kluwer Medknow Publications, 2014)
Background: Dental avulsion is defined as the complete displacement of tooth out of socket along with severed periodontal ligament with or without fracture of the alveolar bone. Reimplantation of the avulsed tooth is considered as a best treatment modality due to its biological and psychological advantages. The viability of periodontal ligament cell on the root surface determines the prognosis of reimplanted tooth. The knowledge of parents regarding important steps to be taken immediately after dental avulsion is considered crucial for success of the treatment. Aim: The study was conducted to evaluate the knowledge and attitude of parents in Chennai with regard to avulsed permanent tooth of their children and their emergency management using a questionnaire. Materials and Methods: The study included 529 parents who accompanied their children, aged between 6 years and 12 years, to the Department of Pedodontics, Saveetha Dental College and Hospitals. Chi-square test was done to evaluate the association between the results and the genders, educational level, and geographical status of the respondents. Results: The study revealed even though 90.7% of parents knew that saving an avulsed permanent tooth is important, but almost one third of the population thought ice water was the best media to transport an avulsed teeth. Conclusion: There is an imperative need for educating the parents regarding management of avulsed tooth for which 87.9% showed interest.